Electrical properties and phase transition behaviors of Sn doped 0.45PZT- 0.55PNN ceramics - Sutjarittangtham K. (2014)
Dielectric properties, and phase transition behaviors of Sn doped 0.45PbZr1/2Ti1/2O3 - 0.55PbNi 1/3Nb2/3O3 ceramics has been investigated. The ceramics were prepared by a normal solid-state method and were characterized, using a variety of techniques. For undoped samples, high relative permittivity of > 21000 (at 1k Hz) was found at the transition temperature of 104°C. With increasing Sn concentration, the degree of diffuse phase transition was enhanced and a linear reduction in the transition temperature was produced. © 2009 American Institute of Physics.